Meningkatkan Keterampilan Vokasional Membuat Vas Bunga dari Pelepah Pisang Melalui Metode Drill bagi Anak Autis - Hikmah Mentari; Fatmawati Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2021)
The research was conducted based on the problems found in SLB Autisma YPPA Padang, there were 5 autistic class X students who had the ability to make handicrafts. But the teacher does not provide variations in the provision of material, the teacher only teaches embroidering material, resulting in children being bored with the material provided by the teacher. The purpose of this study was to prove that the drill method can improve vocational skills in making flower vases from banana leaves for autistic children at SLB Autisma YPPA Padang.The method used is the experimental method in the form of a pre-experiment with the type of one group pretest postest design. The research subjects were 5 children with autism. The pretest and posttest scores were processed using the Wilcoxon sign rank test statistical analysis .The results showed good results, it can be seen from the results of data processing obtained a value of -2.032 b and a probability value or Asymp value . Sig. (2-tailed ) = 0.04 2 is smaller than the probability of yan g has been set at 0, 05. It can be inferred 0.04 2 <0.05, which means the method drill is effective in improving vocational skills make a vase of banana for autistic children at SLB Autisma YPPA Padang.